How well-behaved are revisions to quarterly fiscal data in the euro area? - Krzysztof Bankowski; Thomas Faria; Robert Schall (European Central Bank (ECB), 2022)
Since most macroeconomic data are revised after the initial release both researchers and policy-makers have no choice rather than recognising and understanding the revisions. This paper analyses revisions to the fiscal data in the euro area, also by contrasting them with the 'better-understood' macro revisions. Concretely, the study verifies whether fiscal revisions fulfil requirements to treat them as well-behaved. To this end, we construct a fiscal quarterly real-time dataset, which contains quarterly releases of Government Finance Statistics and which is supplemented by macro variables from Main National Accounts. Fiscal revisions do not satisfy desirable properties expected from well-behaved revisions. In particular, they tend to have a positive bias, they exhibit a big dispersion and they are largely predictable. Also, they are similar to macro revisions, in particular since 2014, which contradicts the often heard view about fiscal data being subject to particularly large revisions.
Keywords: C80; E62; 330; Fiscal policy; real-time data; data revisions